A Comprehensive Genetic Map of the Cattle Genome Based on 3802 Microsatellites - Ihara, Naoya; Takasuga, Akiko; Mizoshita, Kazunori; Takeda, Haruko; Sugimoto, Mayumi; Mizoguchi, Yasushi; Hirano, Takashi; Itoh, Tomohito; Watanabe, Toshio; Reed, Kent M.; Snelling, Warren M.; Kappes, Steven M.; et al.

(untitled) (Genome Research, 2004)
A microsatellite-based high-density genetic map facilitates for fine mapping of hereditary traits of interest, characterization of meiosis, and providing a foundation for physical map construction. Here, we developed a comprehensive genetic map on the basis of >880,000 genotypes across the USDA MARC cattle reference families with a potential genetic resolution of 0.8 cM at the 95% confidence level (∼800 kb in the bovine genome). We incorporated 2325 microsatellites into the second-generation genetic map by linkage analysis based on sex-averaged two-point LOD scores (>3.0), of which 2293 were fine-mapped by multipoint linkage analysis. The new 3160-cM map comprised of 29 sex-averaged autosomal linkage groups and a sex-specific X-chromosome linkage group includes 3960 markers with 2389 positions, resulting in an average interval size of 1.4 cM. More than half (51%) of the total length of the map is covered with intervals of 2.0 cM or less, and the largest gap is a 10.2-cM interval on the X-linkage group. The new map should accelerate fine mapping and positional cloning of genes for genetic diseases and economically important traits in cattle, as well as related livestock species, such as sheep and goat.